a)stiind ca a+b=-23 si c=4,calculati a*c+b*c
b)stiind ca a+b=18 si c=-9,calculati a*c+b*c
c)stiind ca a-b=67 si c=-3 calculati a*c-b*c
d)stiind ca a-b=67 si c=-7 calculati a*c-b*c

Răspuns :

Explicație pas cu pas:

Factorul Comun - Reguli

[tex] \red{\boxed{\bf a \cdot c + b \cdot c = (a + b) \cdot c}} [/tex]

[tex] \red{\boxed{\bf a \cdot c - b \cdot c = (a - b) \cdot c}} [/tex]

a) a * c + b * c = (a + b) * c = -23 * 4 = -92

b) a * c + b * c = (a + b) * c = 18 * (-9) = -162

c) a * c - b * c = (a - b) * c = 67 * (-3) = -201

d) a * c - b * c = (a - b) * c = 67 * (-7) = -469

Alte intrebari